Kegagalan Kemerdekaan New Caledonia Dari Prancis: Studi Kasus Perjuangan Suku Kanak - Akbar, Ridwan Azhari; Firnas, Muhamad Adian; Fitriyanti, Rahmi (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2025)
This study analyzes the causes of the Kanak people's failed struggle in the New Caledonia independence referendum in 2018, 2020, and 2021. The Kanak people are an indigenous people who inhabited New Caledonia before the arrival of the French in 1853. The Kanak people have fought for their independence through referendums stipulated in the 1998 Noumea Agreement. This agreement provides for three referendums, but all referendums failed to make New Caledonia independent. Thus, the third referendum in 2021 marks the end of the Kanak people's struggle for independence, they are legally integrated into the French Republic as a final decision. This study uses the conceptual framework of